The Influence of the Material Specification Plan of Gas Transmission Pipeline Construction on Cost Performance - Girsang, Hamonangan; Lutfiansyah, Yopi; Rochmad, Imbuh (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2025)
The fulfillment of gas networks in industry and households continues to be developed to meet the needs of gas consumers with piping systems in households and industries so that the construction of gas transmission pipeline projects which are the main routes before being distributed to households or certain sectors continues to be carried out, this study aims to find the impact of costs when detailed engineering design of pipes based on the specifications of the pipes used compared to the basic conceptual design. The method used in this study is quantitative, involving field engineering surveys, followed by volume analysis based on work methods, and subsequently unit price analysis. The data generated by the detailed engineering design is compared with the conceptual design volume. An integrated design contractor carries out the construction of a 74-kilometer gas transmission pipeline located on the edge of toll roads and national roads, and its construction implementation. In contrast, the basic conceptual design is carried out by a consultant with an estimated volume of work to be carried out with various work methods, including the Horizontal Directional Drilling method of 5,439 meters, the Auger Boring method of 228 meters, and the Open Alexistoto Cut method of 68,333 meters. According to the technical specifications, the pipe material used varies in each work method, depending on the stress-strain during construction. Integrated design and build contractors are required to perform detailed detailing of conceptual design by verifying through engineering surveys to obtain the necessary volume, following the implementation method associated with using pipe materials for cost management. This study found that the influence of pipe material specifications based on work methods resulted in an 18.3% increase in costs.